HÀM LƯỢNG KIM LOẠI NẶNG TRONG MỘT SỐ LOÀI CÁ KINH TẾ VÙNG BIỂN VEN BỜ QUẢNG NINH - Lê, Quang Dũng; Nguyễn, Việt Linh; Vũ, Văn Tú (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
THE CONTENT OF HEAVY METALS IN COMMERCIAL FISH FROM QUANG NINH COASTIn order to understand heavy metal content in commercial ocean fish from Quang Ninh coast and the risk for human consumption, the content of 8 heavy metals (As, Cd, Co, Cr, Mn, Cu, Zn and Pb) found in the muscles of 4 ocean fish species from Ha Long and Tien Yen is studied. The results of the study indicate that the metal accumulations in the tissues of the 4 species are different and may depend on their habitats and food items. The results also show that the heavy metal levels in the four fish species are within permissible limits set by Ministry of Health and are safe for human consumption. However, the high level of total arsenic in the fish suggests further study.